Internet as a source of information in public health. Part II.The most popular Internet services related to public health information - Bryła, Marek; Stegienta, Grzegorz; Kowalska, Alina; Maniecka-Bryła, Irena (Polish Journal of Public Health, 2009)
This part of the paper concerns the most popular services offered on the Internet in the field of public health. The Internet is the most interactive mass medium in the history of our civilization, as it may have theoretically as many providers as receivers. The Internet is characterized by its attributes of being global and mass. It evolves in quantitative and qualitative sense. New information resources constantly emerge as well as their new categories appear. The information technique becomes more and more powerful and user-friendly. New Internet technologies of a higher level emerge daily. They are sometime called Internet services, which may coexist with older services or even be combined with them, as they function on the basis of the same infrastructure. Nowadays the most popular services include: World Wide Web, e-mail, Internet communicators, P2P, FTP, discussion forums, Telnet. The paper explains each of these services, while we devote the most space to www we discuss, on the one hand, the quality and reliability of information, and on the other hand, transparency, integrity and responsibility of www site owners, we indicate the opportunities called by www pages in the domain of access, to medical journals, libraries, on-line bibliographic databases. Relatively large space is devoted to discussion on the Internet catalogue and browsers. We also raise the issue that webmasters can collect all types of information on user behaviours without their awareness. Since Google has become the most popular browser worldwide, we quote the basic rules of formulating queries in Google.